2014
DOI: 10.1002/zaac.201400093
|View full text |Cite
|
Sign up to set email alerts
|

Two Coordination Polymers Constructed from 5‐(4‐Pyridyl)‐1H‐tetrazole Ligands with Different Organic Carboxylates: Structure and Luminescence Properties

Abstract: Abstract. Two coordination polymers (CPs), namely, [Cu(Hptz) 2 -(Hhba) 2 ] n (1) [Hptz = 5-(4-pyridyl)-1H-tetrazole, H 2 hba = 2-hydroxybenzoic acid] and [Zn 3 (ptz) 2 (hpa) 2 ] n (2) (H2hpa = 2-hydroxy-2-phenylacetic acid), were synthesized by solvothermal reactions. Both complexes were characterized by elemental analysis, infrared spectroscopy, powder X-ray diffraction, thermogravimetric analysis, and single-crystal X-ray diffraction analysis. Compound 1 exhibits a 2D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…A search in the CCDC database concerning six-coordinate metal complexes with a MO 2 N 4 chromophore bearing two monodentate salicylato derivatives as ligands has revealed that in the majority of the reported complexes, especially in the co-existence of monodentate N-donor ligands [70][71][72], flexible N,N′-donor ligands [73][74][75] and planar N,N′,N″,N‴-donor porphyrinato derivatives [76], the salicylato ligands are in trans arrangement [70][71][72][73][74][75][76]; in fewer cases and especially in the co-existence of robust N,N′-donor ligands such as bipy and phen ligands, the salicylato ligands (including the bulky 3-hydroxy-2-naphthoato and 2-hydroxy-3,5-diisopropylbenzoato ligands) were found in cis positions [77][78][79][80], similarly to complex 2.…”
Section: Synthesis and Characterization Of The Complexesmentioning
confidence: 98%
“…A search in the CCDC database concerning six-coordinate metal complexes with a MO 2 N 4 chromophore bearing two monodentate salicylato derivatives as ligands has revealed that in the majority of the reported complexes, especially in the co-existence of monodentate N-donor ligands [70][71][72], flexible N,N′-donor ligands [73][74][75] and planar N,N′,N″,N‴-donor porphyrinato derivatives [76], the salicylato ligands are in trans arrangement [70][71][72][73][74][75][76]; in fewer cases and especially in the co-existence of robust N,N′-donor ligands such as bipy and phen ligands, the salicylato ligands (including the bulky 3-hydroxy-2-naphthoato and 2-hydroxy-3,5-diisopropylbenzoato ligands) were found in cis positions [77][78][79][80], similarly to complex 2.…”
Section: Synthesis and Characterization Of The Complexesmentioning
confidence: 98%